Phenolic Profiling of Berries Waste and Determination of Their Antioxidant Potential - Youyou Jiang; Vigasini Subbiah; Hanjing Wu; Amrit Bk; Javad Sharifi-Rad; Hafiz A. R. Suleria (Journal of Food Quality, 2022)
Berries waste is a major issue in Australia’s annual food wastage, which can reach 7.3 million tonnes. This study assessed the phenolic content and antioxidant potential of four fruit berry wastes, including blueberries (Vaccinium corymbosum), blackberries (Rubus spp.), raspberries (Rubus idaeus), and strawberries (Fragaria spp.), followed by their characterization and quantification. Blueberry wastes were high in phenolic content (total phenolic content: 1.97 ± 0.16 mg GAE/gF.W; total flavonoid content: 220.43 ± 13.15 μg QE/gF.W; total tannins content: 16.47 ± 0.98 μg CE/gF.W), and antioxidant potentials are 2,2′-diphenyl-1-picrylhydrazyl: 2.23 ± 0.17 mg AAE/gF.W; 2,2′-azino-bis-(3-ethylbenzothiazoline-6-sulphonic acid): 1.79 ± 0.09 mg AAE/gF.W; ferric reducing antioxidant power: 68.71 ± 11.11 μg AAE/gF.W (total antioxidant capacity: 1.22 ± 0.03 mg AAE/gF.W). The LC-ESI-QTOF-MS/MS analysis identified 87 compounds from blueberry (57), strawberry (40), raspberry (47), and blackberry wastes (27). Indicated by HPLC quantification, blueberry wastes had higher levels of phenolic acid (syringic acid and coumaric acid) and flavonoid (kaempferol and kaempfero l-3-glucoside). Our study reported that phenolics from berry wastes could be utilized in different food, feed, pharmaceutical, and nutraceutical industries.